2021
DOI: 10.3390/ijerph18179238
|View full text |Cite
|
Sign up to set email alerts
|

An In Vitro Analysis on Polyurethane Foam Blocks of the Insertion Torque (IT) Values, Removal Torque Values (RTVs), and Resonance Frequency Analysis (RFA) Values in Tapered and Cylindrical Implants

Abstract: Background: Several different dental implant microgeometries have been investigated in the literature for use in low-density bone sites. The polyurethane solid rigid blocks represent an optimal in vitro study model for dental implants, because their composition is characterized by symmetrical linear chains of monomers of hexa-methylene sequences producing a self-polymerization process. The aim of the present investigation was to evaluate the primary stability of cylindrical and tapered implants positioned into… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 40 publications
0
7
0
Order By: Relevance
“…Apart from cutting bone/PU material it probably also compresses the bone in lateral direction during insertion. Previous studies have shown higher stability for tapered versus straight dental implants 15,16,22 …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Apart from cutting bone/PU material it probably also compresses the bone in lateral direction during insertion. Previous studies have shown higher stability for tapered versus straight dental implants 15,16,22 …”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have shown higher stability for tapered versus straight dental implants. 15,16,22 5 | CONCLUSION…”
Section: Discussionmentioning
confidence: 99%
“…The dense bone blocks (#40) were characterized by a density of 0.64 g/cc and were laminated on one side with 2 mm of cortical bone (#50). The additional mechanical properties of the bone blocks used in the study are described in the Sawbones catalog [ 6 ].…”
Section: Methodsmentioning
confidence: 99%
“…Implant primary stability is an important parameter in optimal osseointegration and is a critical prerequisite factor for immediate or early loading [ 1 , 2 , 3 ]. Primary implant stability is affected by various factors, such as the implant’s geometry, bone quality and quantity (mainly cortical bone thickness), and the surgical drilling technique used [ 3 , 4 , 5 , 6 , 7 ]. There are also special surgical implant preparation site protocols that are adjusted to the bone type in order to modify and improve the implant’s primary stability [ 7 , 8 ].…”
Section: Introductionmentioning
confidence: 99%
“…Higher implant stability corresponds to a higher ISQ value and several factors can affect these readings. Bone density and the macro‐ and micro‐geometries of the implant have all been shown to have an effect (Comuzzi et al, 2021 ; Gehrke et al, 2015 ; Marquezan et al, 2012 ; Merheb et al, 2018 ; Novellino et al, 2017 ). The influence of SmartPeg tightening has only been scantly assessed to date.…”
Section: Introductionmentioning
confidence: 99%